2023
DOI: 10.1021/acs.orglett.3c01206
|View full text |Cite
|
Sign up to set email alerts
|

Thio(seleno)cyano-difluoroalkylation of Alkenes Using Visible-Light Photocatalysis

Abstract: A mild and efficient three-component thio(seleno)cyano-difluoroalkylation of simple alkenes is demonstrated using an iridium(ruthenium) photocatalyst. This protocol provides a direct and regioselective installation of both C–S(Se)CN [thio(seleno)cyanation] and C–CF (difluoroalkylation) bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, the main research object of these methods is trifluoromethylation or perfluoromethylation; thus, there is still great development space for the difluoromethylene thiocyanation reaction. Very recently, during the preparation of this letter, the Hong group developed a simple and practical method for the thio­(seleno)­cyanation–difluoroalkylation of alkenes via visible-light photoredox catalyst iridium (ruthenium) . In a continuation of our previous reports of copper-catalyzed three-component fluoroalkylation reactions, herein, we report visible-light-induced, copper-catalyzed three-component couplings of an array of alkenes and BrCF 2 CO 2 Et with inorganic compound KSCN as the SCN source, which can be achieved under mild conditions (without the assistance of an external oxidant) to afford thiocyanodifluoroalkylation products in moderate to good yields (Scheme d).…”
mentioning
confidence: 86%
“…However, the main research object of these methods is trifluoromethylation or perfluoromethylation; thus, there is still great development space for the difluoromethylene thiocyanation reaction. Very recently, during the preparation of this letter, the Hong group developed a simple and practical method for the thio­(seleno)­cyanation–difluoroalkylation of alkenes via visible-light photoredox catalyst iridium (ruthenium) . In a continuation of our previous reports of copper-catalyzed three-component fluoroalkylation reactions, herein, we report visible-light-induced, copper-catalyzed three-component couplings of an array of alkenes and BrCF 2 CO 2 Et with inorganic compound KSCN as the SCN source, which can be achieved under mild conditions (without the assistance of an external oxidant) to afford thiocyanodifluoroalkylation products in moderate to good yields (Scheme d).…”
mentioning
confidence: 86%
“…Recently, Molander et al reported the first photocatalytic 1,2-difunctionalization of N -alkenyl amides with BrCF 2 CO 2 Et and other nucleophiles availed by a radical-polar-crossover pathway (Scheme b) . During the preparation of this paper, Hong et al described thio­(seleno)­cyano-difluoroalkylation of alkenes, which uses an expensive Ir-based photocatalyst and has a limited substrate scope and inadequate synthetic yields . Herein, we report a transition metal-, stoichiometric oxidant-, and additive-free, 1,2-thio/selenocyano-difluoro/alkyl-acetylation of simple styrene and alkene derivatives, using 4CzIPN as the organophotocatalyst.…”
mentioning
confidence: 88%
“…3 As there is growing recognition of the significance of radical chemistry in difluoroalkylation reactions, the direct generation of difluoroalkyl radical intermediates using ruthenium- or iridium-based photoredox catalysts mediated by visible light has gained great interest. 4…”
Section: Introductionmentioning
confidence: 99%